2016
DOI: 10.3402/ijch.v75.29528
|View full text |Cite
|
Sign up to set email alerts
|

Liver biochemistry and associations with alcohol intake, hepatitis B virus infection and Inuit ethnicity: a population-based comparative epidemiological survey in Greenland and Denmark

Abstract: Background. Hepatitis B virus (HBV) infection is common in Arctic populations and high alcohol intake has been associated with an increased risk of a number of diseases. Yet, a description of the influence of alcohol intake in persons with HBV infection on liver biochemistry is lacking. Objective. We aimed to describe the association between reported alcohol intake and liver biochemistry taking into account also HBV infection, ethnicity, Inuit diet, body mass index (BMI), gender and age in an Arctic population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Although no interaction was observed in our results, the reason may be the small number of cases (n 38, 2•8 %) in the alcoholic healthy population; however, the number of cases of abnormal levels of ALP in other populations varies from 4•4 to 4•9 %, which may induce low statistical power for inference. This phenomenon indicates that the number of people who drink alcohol with abnormal ALP levels is less than that of other subgroups, suggesting that there is a negative association between alcohol consumption and ALP, which is supported by previous studies (36,37) , although other studies have found no association between alcohol and ALP levels (38,39) . Further studies are needed with a larger sample size to demonstrate this association.…”
Section: Discussionsupporting
confidence: 72%
“…Although no interaction was observed in our results, the reason may be the small number of cases (n 38, 2•8 %) in the alcoholic healthy population; however, the number of cases of abnormal levels of ALP in other populations varies from 4•4 to 4•9 %, which may induce low statistical power for inference. This phenomenon indicates that the number of people who drink alcohol with abnormal ALP levels is less than that of other subgroups, suggesting that there is a negative association between alcohol consumption and ALP, which is supported by previous studies (36,37) , although other studies have found no association between alcohol and ALP levels (38,39) . Further studies are needed with a larger sample size to demonstrate this association.…”
Section: Discussionsupporting
confidence: 72%
“…Of the 79 studies themed Alcohol abuse , only one study focused exclusively on this subject [ 38 ]. 21 studies focused primarily on alcohol abuse, with a secondary focus on other areas such as biological and genetic issues [ 39 , 40 ], cross-addictions [ 41 43 ], migration [ 44 ], violence [ 45 , 46 ], relations with parents and adults outside the family [ 47 – 50 ] and children’s health behaviour [ 51 – 56 ]. In the 57 remaining studies, alcohol use and abuse were supplemented as part of larger national public health surveys or as part of cross-national public surveys.…”
Section: Systematic Mapping Through the Research Focus Questionsmentioning
confidence: 99%